I-V CHARACTERISTIC ANALYSIS OF WATER HYACINTH (EICHHORNIA CRASSIPESS) ACTIVATED CARBON BASED SUPERCAPACITOR ELECTRODE WITH CHEMICAL ACTIVATOR TYPE - Tuloi, Silo Palerius; Tumimomor, Farly Reynol; Nusa, Jeilen N. G (SOSCIED, 2025)
To meet the urgent future energy needs, and the demand for sustainable and renewable energy resources continues to increase, electrical energy storage devices such as supercapacitors are an alternative for biomass-based electrical energy utilization. In this study, water hyacinth samples have been successfully modified into activated carbon from KOH and NaOH activators as supercapacitor electrodes. Chemical activation process using KOH solution concentrations of 3 M, 5 M, 7 M and NaOH 3 M, 5 M, 7 M, with physical activation using a furnace at 750oC produces a voltage with each concentration of 3 M, 5 M, and 7 M KOH of 1.235 V, 1.637 V, 1.715 V current 12.01 mA, 9.59 mA, 6.76 mA and 3, 5 M, and 7 M NaOH 1.012 V, 1.516 V, 1.625 current 10.59 mA, 9.53 mA, 6.09 mA which shows that there is a difference in the value of voltage and electric current in supercapacitor electrodes, with KOH samples with concentrations of 3 M, 5 M, and 7 M, overall KOH is better than the type of activator NaOH. So it can be concluded that the type of activator has a characteristic influence on the voltage and electric current in supercapacitor electrodes